2021
DOI: 10.1186/s12864-021-07561-x
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine-induced changes in myocardial gene transcription are sex-dependent

Abstract: Background Prior work demonstrated that female rats (but not their male littermates) exposed to methamphetamine become hypersensitive to myocardial ischemic injury. Importantly, this sex-dependent effect persists following 30 days of subsequent abstinence from the drug, suggesting that it may be mediated by long term changes in gene expression that are not rapidly reversed following discontinuation of methamphetamine use. The goal of the present study was to determine whether methamphetamine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…These genes were not altered in hearts of adult rats following prenatal exposure to methamphetamine. Likewise, prenatal methamphetamine exposure in the present study induced changes in proteins that have been implicated in heart failure (DDAH2 and Bdh1) and function of the major histocompatibility complex (RT‐1Bb, RT1‐CE7, RT1‐CE15, RT1‐A1) but were not significantly impacted when methamphetamine was administered during adulthood (Chavva et al, 2021 ). Thus, exposure to methamphetamine during either the prenatal period or during early adulthood both results in a female specific phenotype that is characterized by myocardial hypersensitivity to ischemic injury changes in cardiac gene expression that occur predominately in female hearts.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…These genes were not altered in hearts of adult rats following prenatal exposure to methamphetamine. Likewise, prenatal methamphetamine exposure in the present study induced changes in proteins that have been implicated in heart failure (DDAH2 and Bdh1) and function of the major histocompatibility complex (RT‐1Bb, RT1‐CE7, RT1‐CE15, RT1‐A1) but were not significantly impacted when methamphetamine was administered during adulthood (Chavva et al, 2021 ). Thus, exposure to methamphetamine during either the prenatal period or during early adulthood both results in a female specific phenotype that is characterized by myocardial hypersensitivity to ischemic injury changes in cardiac gene expression that occur predominately in female hearts.…”
Section: Discussionsupporting
confidence: 49%
“…This sex‐dependent cardiac phenotype was similar to that observed following prenatal exposure to methamphetamine (Rorabaugh et al, 2016 , 2017 ). RNA sequencing of hearts from these animals identified 340 changes in gene expression 24 h after the final methamphetamine injection (Chavva et al, 2021 ). Similar to the present study, the vast majority (283 out of 340; 83%) of these changes in cardiac gene expression occurred exclusively in female hearts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this process does not appear to be mediated by the neuronal system [63]. Recent research has indicated that GPCRs may also play a role in producing detrimental cardiac effects of Meth, including arrhythmia, fibrosis, cardiomyopathy, and tissue remodeling [64,65]. As depicted in Fig 3A, cAMP interfaces with numerous factors within the GPCR pathway that may induce such cardiovascular effects [66].…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, NPAS2 was comprised in the set of genes found deregulated in myocardial transcriptome upon methamphetamine challenge. These genetic changes showed sexspecific pattern and the number of deregulated genes and the degree of the variation were significantly greater in female hearts respect to male hearts [108]. The role played by altered regulation of circadian genes in the pathogenesis of cardiovascular disease seems to be corroborated also in the case of cerebrovascular events.…”
Section: Npas2 and The Cardiovascular Systemmentioning
confidence: 84%